Level and Predictors of Knowledge of Reproductive Rights Among Haramaya University Students, Eastern Ethiopia: A Cross-Sectional Study - Yuya, Mohammed; Adem, Hassen Abdi; Assefa, Nega; Alemu, Addisu; Umer, Abdurezak Adem; Oljira, Lemessa (Frontiers in Reproductive Health, 2021)
Background: Globally, two-thirds of premature deaths and one-third of the total disease burden in adults are associated with problems that began in adolescent and youth. Global and national acting educational and health policies, strategies and programs designed to promote, implement and improve adolescent and youth sexual and reproductive health services utilization should be responsive, consider the knowledge of reproductive rights and risk factors. This study assessed level and predictors of knowledge of reproductive rights among Haramaya University students in Ethiopia. Methods: An institution based cross-sectional study was conducted among randomly selected Haramaya University students from March 1-24, 2018. Self-administered pretested structured questionnaire was used to collect data from participants. Data were entered using EpiData version 3.1 and analyzed using SPSS version 24. Bivariable and multivariable logistic regression analyses were conducted to identify factors associated knowledge of reproductive rights. Adjusted odd ratio (AOR) with 95% CI was used to report association and significance was declared at P-value less than 0.05. Results: Of 822 total students invited to the study, 812 (98.8%) respondents were participated in the study. A total of 424 (52.2%) (95% CI: 48.8%, 55.4%) students had knowledge of reproductive rights in Haramaya University. Students who were in the fourth and above year of the study [AOR=2.37 (1.58, 3.54)], whose father’s had higher education [AOR=1.89 (1.27, 2.80)], who came from rich family [AOR=1.54 (1.07, 2.21)], in the health faculty [AOR=3.37 (2.17, 5.23)], utilized reproductive health services [AOR=2.81 (2.21, 4.98)] and participated in reproductive health club [AOR=1.77 (1.27, 2.47)] were significantly associated with knowledge of reproductive rights. Conclusions: Around half of the participants had knowledge of reproductive rights. In this study, lack of awareness/information on reproductive health issues and absence of reproductive health services utilization were strong independent predictors of level of knowledge of reproductive rights.